Expert system for mitigating erosion and sedimentation due to storm water during construction activities in Malaysia - Al-Ani I.A.R.; Mohd Sidek L.; Basri N.E.A. (EuroJournals, Inc., 2023)
In this paper, a concise review on the history and application of artificial intelligence and expert system is presented. A review of the effect of erosion and sedimentation that are associated with construction activities on the adjacent water bodies is also presented. The various considerations that must be dealt with in order to ensure a sound and systematic environment for expert system development is also presented. The main features of the development of an artificial intelligence expert system for mitigating erosion and sedimentation during construction activities to the adjacent water bodies were also taken in to consideration in this paper. EuroJournals Publishing, Inc. 2009.